Assessment of ovarian dysfunction induced by environmental toxins: a systematic review - An, Lu; Huang, Yali; Wang, Yunkai; Shen, Shuting; Luo, Xuexing; Liang, Xiaoyan; Lu, Liming; Tang, Chunzhi; Lin, Jinglin; Su, Ting; Zhan, Meiqi; Wang, Dongying; et al. (Frontiers in Public Health, 2025)
ObjectiveThis study systematically assess the potential impact of various environmental pollutants as chemical, airborne, and heavy metal on ovarian function in women, focusing on ovarian reserve such as anti-Müllerian hormone (AMH) and antral follicle count (AFC) as well as hormone levels like follicle-stimulating hormone (FSH) and estradiol (E2). By reviewing epidemiological evidence, this research aims to elucidate the reproductive toxicity of these pollutants and provide scientific support for public health policy to protect reproductive health in women of childbearing age.MethodsFollowing the PRISMA-P guidelines, a comprehensive search was conducted in PubMed, EMBASE, Cochrane Library, and Web of Science databases to include all relevant studies up to July 30, 2024. The Newcastle-Ottawa Scale (NOS) and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach were used to assess study quality.ResultsThis study ultimately included 40 cohort study reports derived from 33 distinct studies that analyzed the effects of 20 pollutant types on ovarian function. Results indicate that pollutants, such as perfluoroalkyl and polyfluoroalkyl substances (PFAS), phthalates (PAEs), triclosan, Polychlorinated Biphenyls (PCBs), PM2.5, and SOX, have a significantly negative impact on ovarian function, especially among younger women (<35 years). Long-term exposure to particulate matter (PM)2.5 and PM10 is associated with a substantial decrease in ovarian reserve, while heavy metals (e.g., lead and cadmium) also demonstrate reproductive toxicity. However, these conclusions require validation due to both methodological limitations in the original studies (e.g., heterogeneous exposure assessments and residual confounding) and challenges in evidence synthesis (e.g., inconsistent outcome measures across cohorts), highlighting the need for further research to address these constraints.ConclusionThis review underscores that specific pollutants (e.g., PCBs, PFAS, PM) pose substantial risks to reproductive health in women of childbearing age, particularly in highly polluted environments. The findings underscore the importance of regular ovarian health monitoring, especially for women at higher risk due to occupational or environmental factors.Systematic review registrationPROSPERO CRD42024567744 (accessible at https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024567744).